Legal Protection for Victims of Sexual Harassment on Social Media from the Perspective of Islamic Criminal Law - Epan Apanda; Noor Azizah (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2023)
Sexual harassmentn social media has become a significant issue in the context of law and digital security in this era. This phenomenon has the potential to harm individuals seriously and requires effective legal protection. This research uses a qualitative approach, a type of normative juridical research, to explore how current laws and policies handle cases of Sexual harassment on social media. The research results show that even though there is a positive legal framework in place, law implementation and enforcement still face challenges in handling complex cases of Sexual harassment in the digital realm. Protection for victims of Sexual harassment needs to be improved through broader education about digital ethics, increasing law enforcement capacity, and improving regulations that are more responsive to the dynamics of modern social media. From the perspective of Islamic criminal law, the protection of dignity and social justice is also highly upheld, with rehabilitation efforts to change the behavior of perpetrators.